MORPHOLOGICAL AND WORD-MAKING FEATURES IN ENGLISH AND UZBEK - Babajanova Iqbol Salomaddinovna (Modern American Journals, 2025)
In this article, research on today's cognitive linguistics is analyzed scientifically and mazariously. The historical roots of word-making in English and Uzbek, as well as the scientific approaches of linguistic scientists, were studied analytically and the author's relationship was expressed. Aspects of commonality and specificity between the two languages were analyzed.
Keywords: Language, linguistics, morphology, word making, prgamatics, semantics, syntax, phonetics.